Successful treatment of idiopathic tetanus using metronidazole, magnesium, and acepromazine in Hanwoo (Korean indigenous cattle) yearling bull - Kim, Youngjun; Ku, Ji-Yeong; Lee, Kichan; Moon, Bo-Youn; Ha, Seungmin; Choi, Kyoung-Seong; Park, Jinho (Frontiers in Veterinary Science, 2023)
Bovine tetanus is a serious infectious disease of the central nervous system caused by the exotoxin produced by Clostridium tetani and is characterized by persistent tension and spasm of the rhabdomyocytes. Currently, many studies have focused on diagnosing tetanus; however, only a few studies on treatment methods have been conducted. Therefore, cattle with tetanus have been treated using symptomatic therapy. In this case, severe muscle spasticity and spasms were observed in a 9-month-old Hanwoo (Korean indigenous cattle) bull, and aspartate aminotransferase and creatine kinase levels were increased in serum biochemical tests. Clinically, bovine tetanus was strongly suspected, and metronidazole was administered orally for 5 days. To treat the intensifying bloat, a temporary rumenostomy was performed on the third day of onset, and the toxin gene (tetanospasmin) of C. tetani was amplified by polymerase chain reaction analysis from the collected ruminal fluid. Magnesium and sedatives (acepromazine) were administered for 7 days to treat muscle spasticity and spasms. Muscle spasticity and spasm markedly improved, and the bull stood up from the lateral recumbent position. On the 17th day after onset, all tetanus-related symptoms resolved and a normal diet was started. Our findings demonstrated that treatment with metronidazole, magnesium, and acepromazine was effective in the bull with tetanus.